2007
DOI: 10.1093/intimm/dxm114
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of IL-6 signaling pathway prevents CD4+ T cell-mediated colitis in a Th17-independent manner

Abstract: Naive CD4(+) T cells rapidly proliferate to generate effector cells after encountering an antigen and small numbers survive as memory T cells in preparation for future immunological events. In the present work, adoptive transfer of naive CD4(+) T cells into RAG2(-/-) mice caused the generation of memory-type effector T cells including T(h)1, T(h)2, T(h)17 and regulatory T cells, and eventually induced T cell-dependent colitis. We found here that blocking of the IL-6R with a specific mAb remarkably inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 40 publications
4
48
0
1
Order By: Relevance
“…46 Another important result from these studies is the confirmation that mucosal pathology mediated by IL-23 can occur in a T H 17-independent manner. Although 2 prior studies 47,48 have also made this observation, the mechanism by which this occurred was not elucidated. Our studies now clearly establish the existence of an alternative pathway whereby the proinflammatory effects of IL-23 in the colon are mediated through secretion of IFN-␥.…”
Section: Role Of Il-23 In Organ-specific Pathology In Gvhd 2359mentioning
confidence: 93%
“…46 Another important result from these studies is the confirmation that mucosal pathology mediated by IL-23 can occur in a T H 17-independent manner. Although 2 prior studies 47,48 have also made this observation, the mechanism by which this occurred was not elucidated. Our studies now clearly establish the existence of an alternative pathway whereby the proinflammatory effects of IL-23 in the colon are mediated through secretion of IFN-␥.…”
Section: Role Of Il-23 In Organ-specific Pathology In Gvhd 2359mentioning
confidence: 93%
“…Accordingly, we found that Th17 cells isolated using an IL-17F reporter transgene induced severe colitis that was associated with recovery of Th1-like cells derived from the Th17 precursors (11). In view of findings that T cells deficient for IL-17A induced colitis that is indistinguishable from (17,18) or more severe than controls, and this disease was associated with increased frequencies of Th1-like cells (19), these results are consistent with a pathogenic role for Th1-like cells that emerge from Th17 precursors.…”
mentioning
confidence: 87%
“…Treatment of RAG1 mice that received IL-17F-null T cells with a neutralizing anti-IL-17A antibody significantly suppresses disease, indicating redundant biological effects of IL-17A and IL-17F. 48 Similarly Noguchi et al 49 showed that colitis induced in RAG mice by transfer of naive CD4þ T cells prepared from IL-17-knockout mice does not differ in terms of severity from that induced by transfer of wildtype cells. The reason why these studies provided us with different results remains unknown.…”
Section: Evidence Supporting the Anti-inflammatory Actions Of Il-17a mentioning
confidence: 99%